Theoretical Evidence for the Distance-Dependent Photoinduced Electron Transfer of Porphyrin-Oligothiophene-Fullerene Triads - Shan Zhang; Yuanzuo Li; Jing Liu; Meiyu Zhao; Yueyi Han; Yong Ding; Peng Song; Fengcai Ma (International Journal of Photoenergy)
The ground and excited state properties of nT-C60 dyads and Por-nT-C60 triads (n=4, 8, and 12) have been theoretically investigated by using the time-dependent density functional theory together with a set of extensive multidimensional visualization techniques. The results reveal that the length of the nT moiety strongly influences the charge transfer characters of these systems. The charge transfer ability is largely strengthened by introducing the porphyrin group and decreases with the length of the nT moiety. Also the adjustment of the electron transport mode of Por-nT-C60 triads by the length of the nT moiety was visualized. It is found that Por*-4T-C60 shows predominantly the energy transfer process generating Por-4T-1C60* but the charge transfer becomes predominant for other triads, such as the direct formation of Por∙+-12T-C60∙− via Por*-12T-C60. Furthermore, the process of